Frequency-specific alternations in the amplitude of low-frequency fluctuations in chronic tinnitus - Chen, Yu-Chen; Xia, Wenqing; Luo, Bin; Muthaiah, Vijaya P. K.; Xiong, Zhenyu; Zhang, Jian; Wang, Jian; Salvi, Richard; Teng, Gao-Jun (Frontiers in Neural Circuits, 2015)
Tinnitus, a phantom ringing, buzzing or hissing sensation with potentially debilitating consequences, is thought to arise from aberrant spontaneous neural activity at one or more sites within the central nervous system; however, the location and specific features of these oscillations are poorly understood with respect to specific tinnitus features. Recent resting-state functional magnetic resonance imaging (fMRI) studies suggest that aberrant fluctuations in spontaneous low-frequency oscillations (LFO) of the blood oxygen level-dependent (BOLD) signal may be an important factor in chronic tinnitus; however, the role that frequency-specific components of LFO play in subjective tinnitus remains unclear. A total of 39 chronic tinnitus patients and 41 well-matched healthy controls participated in the resting-state fMRI scans. The LFO amplitudes were investigated using the amplitude of low-frequency fluctuation (ALFF) and fractional ALFF (fALFF) in two different frequency bands (slow-4: 0.027-0.073 Hz and slow-5: 0.01-0.027 Hz). We observed significant differences between tinnitus patients and normal controls in ALFF/fALFF in the two bands (slow-4 and slow-5) in several brain regions including the superior frontal gyrus (SFG), inferior frontal gyrus, middle temporal gyrus, angular gyrus, supramarginal gyrus, and middle occipital gyrus. Across the entire subject pool, significant differences in ALFF/fALFF between the two bands were found in the midbrain, basal ganglia, hippocampus and cerebellum (Slow 4>Slow 5), and in the middle frontal gyrus, supramarginal gyrus, posterior cingulate cortex, and precuneus (Slow 5>Slow 4). We also observed significant interaction between frequency bands and patient groups in the orbitofrontal gyrus. Furthermore, tinnitus distress was positively correlated with the magnitude of ALFF in right SFG and the magnitude of fALFF slow-4 band in left SFG, whereas tinnitus duration was positively correlated with the magnitude of ALFF in right SFG and the magnitude of fALFF slow-5 band in left SFG. Resting-state fMRI provides an unbiased method for identifying aberrant spontaneous LFO occurring throughout the central nervous system. Chronic tinnitus patients have widespread abnormalities in ALFF and fALFF slow-4 and slow-5 band which are correlated with tinnitus distress and duration. These results provide new insights on the neuropathophysiology of chronic tinnitus; therapies capable of reversing these aberrant patterns may reduce tinnitus distress.